1996
DOI: 10.1089/dna.1996.15.17
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine Methyltransferase Pharmacogenetics: Human Gene Cloning and Characterization of a Common Polymorphism

Abstract: Thiopurine methyltransferase (TPMT) catalyzes the S-methylation of thiopurine drugs. Individual variation in the toxicity and therapeutic efficacy of these drugs is associated with a common genetic polymorphism that controls levels of TPMT activity and immunoreactive protein in human tissues. Because of the clinical significance of the "pharmacogenetic" regulation of this enzyme, it would be important to clone the gene for TPMT in humans and to study the molecular basis for the genetic polymorphism. As a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
242
2
11

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 292 publications
(266 citation statements)
references
References 34 publications
11
242
2
11
Order By: Relevance
“…Furthermore, as pointed out previously, there is a strong correlation between relative levels of TPMT activity in the RBC and in other human tissues (Woodson et al, 1982;Szumlanski et al, 1992). Following the cloning of the TPMT gene and characterization of its most important polymorphisms (Szumlanski et al, 1996;Tai et al, 1996), determination of TPMT genotype was also shown to be useful for individualizing thiopurine drug therapy. However, both genotyping and phenotyping have their limitations.…”
Section: Tpmt Genetic Polymorphism: Discovery and Clinical Significancementioning
confidence: 86%
See 4 more Smart Citations
“…Furthermore, as pointed out previously, there is a strong correlation between relative levels of TPMT activity in the RBC and in other human tissues (Woodson et al, 1982;Szumlanski et al, 1992). Following the cloning of the TPMT gene and characterization of its most important polymorphisms (Szumlanski et al, 1996;Tai et al, 1996), determination of TPMT genotype was also shown to be useful for individualizing thiopurine drug therapy. However, both genotyping and phenotyping have their limitations.…”
Section: Tpmt Genetic Polymorphism: Discovery and Clinical Significancementioning
confidence: 86%
“…Of the allozymes studied by Salavaggione et al (2005), TPMT*3A, *3B, *3C and *2 displayed the most striking effects. This phenomenon was first observed a decade ago when TPMT*3A, *3B and *3C were initially described (Szumlanski et al, 1996). In the course of those early experiments, these three allozymes, as well as WT TPMT, were expressed in COS-1 cells, and Western blot analysis was performed.…”
Section: Tpmt: Functional Genomics and Molecular Mechanismsmentioning
confidence: 90%
See 3 more Smart Citations